ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN RUMAH TANGGA PETANI DI DAERAH PROGRAM PNPM MANDIRI PEDESAAN (Studi Kasus Desa Balerejo Kecamatan Dempet Kabupaten Demak Tahun Pelaksanaan 2012) - Mirah Titimiranti; Lutfi Aris Sasongko; Aniya Widiyani (Universitas Wahid Hasyim, 2016)
This study aims to determine the socio-economic characteristics and factors affecting farmer’s income level on PNPM Mandiri Pedesaan region in Tempel Sub Village Balerejo Village of Dempet District Demak Regency. Sampling method with a purposive sampling method. Consisted of 30 respondents of benefit recipients and 30 respondents non benefit recipients. This research using multiple linier regression. The result showed that cooficient of determination 0.775. This value indicated that independent variables effect is 77.5 percent, while the remaining 22,5 percent is explained by other variables. Anova test showed the value of 64.413 with significance probability value of 0.000. Partial test showed the variables education and participation has a significance value of 0.000 and age variable has no significant influence. Keyword : income level, PNPM Mandiri Pedesaan, Demak Regency